Relations of mindfulness facets with psychological symptoms among individuals with a diagnosis of obsessive–compulsive disorder, major depressive disorder, or borderline personality disorder. (25th March 2018) - Didonna, Fabrizio; Rossi, Roberta; Ferrari, Clarissa; Iani, Luca; Pedrini, Laura; Rossi, Nicoletta; Xodo, Erica; Lanfredi, Mariangela
Abstract : Objectives: To explore differences in mindfulness facets among patients with a diagnosis of either obsessive–compulsive disorder (OCD), major depressive disorder (MDD), or borderline personality disorder (BPD), and healthy controls (HC), and their associations with clinical features. Design and method: One hundred and fifty‐three patients and 50 HC underwent a clinical assessment including measures of mindfulness (Five Facets Mindfulness Questionnaire – FFMQ), psychopathological symptoms (Symptom Check List‐90‐R), dissociation (Dissociative Experience Scale), alexithymia (Alexithymia Scale 20), and depression (Beck Depression Inventory‐II). Analysis of variance (ANOVA) and analysis of covariance (ANCOVA) were performed to assess differences in mindfulness scores and their associations with clinical features. Results: The three diagnostic groups scored lower on all mindfulness facets (apart from FFMQ observing ) compared to the HC group. OCD group had a significant higher FFMQ total score (FFMQ‐TS) and FFMQ acting with awareness compared to the BPD group, and scored higher on FFMQ describing compared to BPD and MDD groups. The scores in non‐judging facet were significantly lower in all the three diagnostic groups compared to the HC group. Interestingly, higher FFMQ‐TS was inversely related to all psychological measures, regardless of diagnostic group. Conclusions: Deficits in mindfulness skills were present in all diagnostic groups. Furthermore, we found disease‐specific relationships between some mindfulness facets and specific psychological variables. Clinical implications are discussed. Practitioner points: The study showed deficits in mindfulness scores in all diagnostic groups compared to a healthy control group. Overall, mindfulness construct has a significantly negative association with indexes of global distress, dissociative symptoms, alexithymia, and depression. Mindfulness‐based interventions in clinical settings should take into account different patterns of mindfulness skills and their impact on disease‐specific maladaptive cognitive strategies or symptomatology.